Effects of endurance training on skeletal muscle mitochondrial function in Huntington disease patients - Mueller, Sandro Manuel; Gehrig, Saskia Maria; Petersen, Jens A.; Frese, Sebastian; Mihaylova, Violeta; Ligon-Auer, Maria; Khmara, Natalia; Nuoffer, Jean-Marc; Schaller, André; Lundby, Carsten; Toigo, Marco; Jung, Hans H. (Orphanet journal of rare diseases, 2017)
Background Mitochondrial dysfunction may represent a pathogenic factor in Huntington disease (HD). Physical exercise leads to enhanced mitochondrial function in healthy participants. However, data on effects of physical exercise on HD skeletal muscle remains scarce. We aimed at investigating adaptations of the skeletal muscle mitochondria to endurance training in HD patients. Methods Thirteen HD patients and 11 healthy controls completed 26 weeks of endurance training. Before and after the training phase muscle biopsies were obtained from M. vastus lateralis . Mitochondrial respiratory chain complex activities, mitochondrial respiratory capacity, capillarization, and muscle fiber type distribution were determined from muscle samples. Results Citrate synthase activity increased during the training intervention in the whole cohort ( P = 0.006). There was no group x time interaction for citrate synthase activity during the training intervention ( P = 0.522). Complex III ( P = 0.008), Complex V ( P = 0.043), and succinate cytochrome c reductase ( P = 0.008) activities increased in HD patients and controls by endurance training. An increase in mass-specific mitochondrial respiratory capacity was present in HD patients during the endurance training intervention. Overall capillary-to-fiber ratio increased in HD patients by 8.4% and in healthy controls by 6.4% during the endurance training intervention. Conclusions Skeletal muscle mitochondria of HD patients are equally responsive to an endurance-training stimulus as in healthy controls. Endurance training is a safe and feasible option to enhance indices of energy metabolism in skeletal muscle of HD patients and may represent a potential therapeutic approach to delay the onset and/or progression of muscular dysfunction. Trial registration ClinicalTrials.gov NCT01879267 . Registered May 24, 2012.